Blocking autophagy enhances meloxicam lethality to hepatocellular carcinoma by promotion of endoplasmic reticulum stress. (20th October 2015) - Zhong, Jingtao; Dong, Xiaofeng; Xiu, Peng; Wang, Fuhai; Liu, Ju; Wei, Honglong; Xu, Zongzhen; Liu, Feng; Li, Tao; Li, Jie
Abstract: Objectives: Meloxicam, a selective cyclooxygenase‐2 (COX‐2) inhibitor, has been demonstrated to exert anti‐tumour effects against various malignancies. However, up to now, mechanisms involved in meloxicam anti‐hepatocellular carcinoma effects have remained unclear. Materials and methods: Cell viability and apoptosis were assessed by CCK‐8 and flow cytometry. Endoplasmic reticulum (ER) stress and autophagy‐associated molecules were analysed by western blotting and immunofluorescence assay. GRP78 and Atg5 knock‐down by siRNA or chemical inhibition was used to investigate cytotoxic effects of meloxicam treatment on HCC cells. Results: We found that meloxicam led to apoptosis and autophagy in HepG2 and Bel‐7402 cells via a mechanism that involved ER stress. Up‐regulation of GRP78 signalling pathway from meloxicam‐induced ER stress was critical for activation of autophagy. Furthermore, autophagy activation attenuated ER stress‐related cell death. Blocking autophagy by 3‐methyladenine (3‐MA) or Atg5 siRNA knock‐down enhanced meloxicam lethality for HCC by activation of ER stress‐related apoptosis. In addition, GRP78 seemed to lead to autophagic activation via the AMPK–mTOR signalling pathway. Blocking AMPK with a chemical inhibitor inhibited autophagy suggesting that meloxicam‐regulated autophagy requires activation of AMPK. Conclusions: Our results revealed that both ER stress and autophagy were involved in cell death evoked by meloxicam in HCC cells. This inhibition of autophagy to enhance meloxicam lethality, suggests a novel therapeutic strategy against HCC.